Sharing economy as economy of the future (Economic and Political Thought, 2014)
The article presents modern concepts of economics – sharing economyalso called collaborative economy. According to the new principle, access isa new form of ownership – access to goods and services is becoming a newform of ownership. We no longer have to be owners of goods or servicesin order to use them as a consumer or an end user. In connection with thedevelopment of the Internet throughout the world, thousands of companieshave been created that base their business model on sharing economy. Thereare more and more goods and services all over the world, which you donot need to own, but you can still use them and benefit from using thesethings. There is no doubt that this new global movement changes the wayin which future economy will work. This paper provides an analysis of thecurrent global trend of sharing economy on the basis of the results of a surveyconducted by the agency Havas Worldwide in partnership with Market ProbeInternational. 10 574 people aged over 16, representing 29 markets took partin the survey. Sharing economy is currently a very broad term, which coversnot only sharing bicycles, cars and houses, but also common activities suchas cooking. This new concept is growing rapidly across the world, so weshould try to analyse how these companies operate and how they will workin the future. The author of the article tries to predict and describe possibletrends in the development of sharing economy in the future and possible risksassociated with it.